Climate change impact on the architecture and built environment dwellers’ well-being in Niger Delta Region: a systematic review - Dimuna, Kingsley O.; Ekhaese, Eghosa N.; Ndimako, Onyedikachukwu O. (Frontiers in Climate, 2024)
Climate change resulting from weather conditions has recently attracted global attention and concern; such variations have impacted architecture and the built environment, especially on the urban dweller’s well-being and other associated urban problems. This systematic review investigates the effects of climate change on the environment and architecture in the Niger Delta Area of Nigeria and the potential consequences for inhabitants well-being through a systematic review of scholarly literature from Google Scholar, ResearchGate, Science Direct and Scopus covering the period from 2019 to 2024. The study synthesizes current literature, using rigorous inclusion criteria to find relevant studies conducted globally. It involves an assessment procedure that resulted in 25 articles for analysis. The core of the problem lies in the gaps in that climate change has negatively impacted the environment, architecture and building construction mechanism in the Niger Delta Region. This review systematically observes the methodologies in the selected studies to create a standardized framework for future research using a hybrid review approach. Results reveal that the ongoing incidences of perennial flooding in the region are attributable to climate change across different geographic locations and seasons. The authors proffered some recommendations to mitigate these impacts for future research. However, this systematic review of climate change’s impact on the architecture and dwellers’ well-being in the built environment in the Niger Delta presents valued insights for policymakers and urban health practitioners, enhances the urban built environment health systems resilience, and well organize communities for the climate change challenges.